КОНФУЦИАНСКАЯ ЭТИКА ВОЙНЫ В КОНТЕКСТЕ ДРЕВНЕКИТАЙСКОГО МИФА О ТРАНЗИТЕ ВЛАСТИ - КОЧЕРОВ, Олег Сергеевич (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
The paper analyzes ethical views on war held by the authors of the classical Confucian treatises, Lunyu and Mengzi, in the context of their attitude towards the characters of the ancient Chinese power transition myth. In terms of ethics of war, Mengzi differs from Lunyu in the following aspects: prioritization of justice over political order; emphasis on legitimacy, not legality; people-orientedness over norm-orientedness; development of the jus in bello discourse; permissibility of rebellion, which entails positive assessment of Wu-wang’s campaign, and critique of its objectors, Boyi and Shuqi.